The fauna and summer bird population of the Karagai Biosphere Reserve (Chelyabinsk Oblast) - V. A. Gashek; V. D. Zakharov; B. V. Krasutskiy; D. A. Yasko (Трансформация экосистем)
Based on the results of ornithological studies, conducted in the Karagai Biosphere Reserve in 2008–2022, a list of bird species has been compiled. It consists of 134 (including 118 breeding or, probably, breeding) species. In 2006, chaffinch and tree pipit dominated in number in forest biotopes. The group of subdominants included willow tit, common chiffchaff, great tit and pied flycatcher. In 2018, most numerous chaffinch and tree pipit slightly outnumbered great tit, common redstart, common chiffchaff, and great spotted woodpecker. In ecological groups, dendrophiles prevailed (63% of all species). The share of limnophiles made up 17%, campophiles and sclerophiles – 10% each. Characteristic of the taiga complex breeding (or expected to nest), species, i.e. hazel grouse, deaf cuckoo, long-tailed and great grey owls, bramble finch, common crossbill, and common bullfinch were encountered.